Creative Self-Expression as a Scientific Problem - Jafarova, Olena (Pedagogical Discourse, 2012)
On the basis of different conceptions analysis, in this article we define the essence of conception “creative self-expression” and its functions. We have defined the place that self-expression takes in the system of conceptions: self-realization, self-development, and self-actualization. We have pointed out the components of inner world: cognitive, emotional-evaluative, and behavioral. We have come to the conclusion that the phases of creative self-expression are close to the phases of creative activity. In the end we have brought out the need to activate the creative self-expression in childhood.